Attitudes towards translanguaging: how future teachers perceive the meshing of Arabic and English in children's storybooks. Issue 3 (16th March 2021) - al-Bataineh, Afaf; Gallagher, Kay
ABSTRACT: This paper seeks to identify the attitudes of bilingual future teachers towards translanguaging when writing stories for bilingual young learners, and to understand the various forces that shape their attitudes. Translanguaging, in the context of this study, refers to the dynamic and intended shuttling between languages or dialects. An assignment in a Children's Literature course in a bilingual university in the United Arab Emirates required participants to move across Modern Standard Arabic, their native Emirati Arabic, and English both between and within sentences, and to allocate equal weight to these languages/varieties in the meaning-making process. As an ethnographic study, participants' attitudes were elicited at various stages of the research project. The findings indicate that they held paradoxical and ambivalent attitudes towards translanguaging, and that language ideology played a crucial role in determining their attitudes, as well as the degree to which translanguaging in writing was accepted or rejected.